Comparative investigation of double slope solar still by incorporating different types of collectors: A mini review. (2021) - Patel, Raj Vardhan; Bharti, Kiran; Singh, Gaurav; Mittal, Gaurav; Singh, Desh Bandhu; Yadav, Anshul
Abstract: The fresh water scarcity is the contemporary issue for all areas around the globe due to available water getting polluted by various anthropogenic activities. The conventional Reverse osmosis (RO) system for purification of water needs electricity for its working and generation of electricity by conventional source emits polluting elements which is detrimental for the environment. Unlike conventional RO system, solar based water purification system called solar still is environment friendly and has the potential to mitigate the contemporary issue of fresh water scarcity. Various designs and material selection has been reported by researchers around the globe. In this review work, an effort by authors have been put to summarize double slope solar based water purification units by incorporating different kinds of collectors. After studying different solar based double slope water purification units, a comparison has been made on the basis of yield. It has been concluded that solar based double slope water purification unit incorporated with evacuated tubular collectors is better than other similar setups.